Development of Android-Based Learning Media in Simulation and Digital Communication Subjects - Nikmatul Khairani; Hasan Maksum (STAI Miftahul Ula Nganjuk, 2020)
The research’s aim to get a valid, practical, and effective android-based learning media in the subjects of simulation and digital communication. This android-based learning media is designed to be able to improve the understanding of learners so as to improve learning outcomes. This study uses research and development method (Rand D)with 4-D development procedure (define, design, develop, and desseminate). The research subjects were students of class X Software Engineering at SMK Negeri 1 Sintuk Toboh Gadang consisting of 27 students. Data analysis techniques using N gain test. , as well as effective in improving the understanding of learners obtained from the calculation of the gain score obtained by 0.63 with a moderate category. So it can be concluded that android-based learning media is effective to be used as a media for simulation learning and digital communication.